PP.18.06: ARTERIAL STIFFNESS AND LEFT ATRIAL VOLUME INDEX IN HYPERTENSIVE AND NORMOTENSIVE SUBJECTS. (June 2015) - Rojek, M.; Rajzer, M.; Czarnecka, D.
Abstract : Objective: Comparison of the relationship between arterial stiffness indices and left atrial volume index (LAVI) in hypertensive and normotensive subjects. Design and method: Study and control group were randomly recruited among Morawica town inhabitants. Study group consisted of 41 treatment- naive hypertensives (AH), stage 1. or 2. (20 men and 21 women). Control group (NonAH), consisted of 60 normotensives (32 men and 28 women). Necessary anthropometric and demographic data has been collected in the form of questionnaire. In both groups following examinations were performed: office blood pressure measurements on the non-dominant arm after 10 min. rest with the use of Omron M5-I; arterial stiffness measurements i.e. carotid-femoral pulse wave velocity (PWV) and central blood pressure (cSBP, cDBP, cPP) with use of SphygmoCor® device; echocardiographic left atrium volume determination (LAV) according to Simpson method with use of VIVID-7 GE device followed by LAVI calculation (LAVI = LAV/body surface area). Results: AH group was older (56, 9 ± 9, 6 vs 50, 2 ± 7, 9 yrs, p = 0, 0002) exhibiting higher BMI (28, 2 ± 9, 0 vs 26, 3 ± 5, 9 kg/m2, p = 0, 03) and higher office SBP (149, 5 ± 15, 7 vs 138, 6 ± 20, 1 mmHg, p = 0, 04) and DBP (91, 1 ± 8, 4 vs 85, 7 ± 12, 8, p = 0, 02) than NonAH group. Compared groups did not differ within PWV values, while cSBP (136, 3 ± 15, 0 vs 126, 8 ± 20, 0 mmHg, p = 0, 02) and cDBP (90, 8 ± 7, 0 vs 84, 9 ± 12, 3 mmHg, p = 0, 01) were higher in AH group. LAVI was significantly higher in AH group than in NonAH group (27, 8 ± 9, 5 vs 24, 3 ± 6, 6 ml/m2, p = 0, 003). In AH group LAVI correlated positively only with cSBP (r = 0, 33, p = 0, 04). In NonAH group, LAVI correlated positively with age (r = 0, 27, p = 0, 03), BMI (r = 0, 39, p = 0, 02) and cSBP (r = 0, 27, p = 0, 04). Conclusions: Hypertensive subjects are characterized by higher values of left atrial volume index. In this group, left atrial volume index depends mainly on central systolic blood pressure, while the factors determining left atrial volume index in the group of normotensives are central systolic blood pressure and moreover, age and body mass index.